Quantification of fibrosis and mast cells in the tissue response of endodontic sealer irradiated by low-level laser therapy - Camargo Villela Berbert, Fabio Luiz [UNESP]; Sivieri-Araujo, Gustavo; Oliveira Ramalho, Lizeti Toledo [UNESP]; Lima Pereira, Sanivia Aparecida; Rocha Rodrigues, Denise Bertulucci; Sivieri de Araujo, Marcelo (Springer London Ltd, 2011)
Low-level laser therapy (LLLT) accelerates tissue repair. Mast cells induce the proliferation of fibroblasts and the development of local fibrosis. The objective of this study was to quantify fibrosis rate and mast cells in connective tissue after endodontic sealer zinc oxide and eugenol (ZOE) was implanted and submitted to LLLT, immediately after implant and again 24 h later. Sixty mice were distributed into three groups: GI, GII, and GIII (n = 20). In GI, the tubes filled with Endofill were implanted in the animals and were not irradiated with LLLT. In GII, the tubes containing Endofill were implanted in the animals and then irradiated with red LLLT (InGaAIP) 685-nm wavelength, D=72 J/Cm(2), E = 2 J, T=58 s, P=35 mW, and in GIII, the tubes with Endofill were implanted and irradiated with infrared LLLT (AsGaAl) 830-nm wavelength, D=70 J/Cm(2), E = 2 J, T=40 s, P=50 mW. After 7 days and 30 days, the animals were killed. A series of 6-mu m-thick sections were obtained and stained with Toluidine Blue and Picrosirius and analyzed under a standard light microscope using a polarized light filter for the quantification of fibrosis. The statistics were qualitative and quantitative with a significance of 5%. The irradiation with LLLT did not offer improvement in the fibrosis rate, however, it provided a significant decrease in the concentration of independent mast cells for the period studied.
Keywords: Endodontics; Zinc oxide and eugenol sealer; Lasers; Fibrosis; Mast cells